Digital Encyclopedia of Applied Physics 2016
DOI: 10.1002/3527600434.eap780
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Hot Electron Bolometers and Transition Edge Sensors

Abstract: The article contains sections titled: Introduction The Energy Scenario and Timescales The Hot Electron Bolometer Transition Edge Sensor The Main Physical Parameters Recent Achievements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Worth mentioning is the development of quantum non-demolition detectors for either cavity [8,27] or itinerant [13,14] photons, which require no absorption and preserve the photon number [1]. Superconducting transition-edge sensors operating as bolometers show sharp resistance increase upon the absorption of photons [28]. These devices typically work at frequencies above THz, but extensions at frequencies down to 90 GHz are in progress [26].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Worth mentioning is the development of quantum non-demolition detectors for either cavity [8,27] or itinerant [13,14] photons, which require no absorption and preserve the photon number [1]. Superconducting transition-edge sensors operating as bolometers show sharp resistance increase upon the absorption of photons [28]. These devices typically work at frequencies above THz, but extensions at frequencies down to 90 GHz are in progress [26].…”
Section: State Of the Artmentioning
confidence: 99%
“…These devices typically work at frequencies above THz, but extensions at frequencies down to 90 GHz are in progress [26]. Additionally, superconducting hot electron bolometers are operated above 300 GHz [28]. Detection schemes based on opto-electro-mechanical systems using mechanical resonators with coupled microwave and optical cavities have also been theoretically proposed [29][30][31].…”
Section: State Of the Artmentioning
confidence: 99%
“…Using EM multimode horns to collect large microwave power, they can achieve better signal-to-noise ratio than single mode bolometers, but they need to work at higher temperatures. In fact, considering that the average optical power is about 10 pW and the thermal conductance G must be ≥ 50 pW/K, to meet the bolometer time constant requirement τ 10 ms, it is necessary a TC ≃ 500 mK [4], [5]. It has been reported that titanium TES have TC as high as 0.6 K, but it is strongly dependent on fabrication processes and substrates [6]- [9].…”
Section: Introductionmentioning
confidence: 99%